2014
DOI: 10.1002/lpor.201400022
|View full text |Cite
|
Sign up to set email alerts
|

Advances in vanadate laser crystals at a lasing wavelength of 1 micrometer

Abstract: Sapphire, garnet and vanadate crystals are the most prominent optical materials, and vanadates play important roles in optics, especially in lasers and nonlinear optics. Neodymium‐doped yttrium vanadate (Nd:YVO4) is representative and available commercially. Based on Nd:YVO4, several vanadate crystals are being developed with the goal of fulfilling the need for differential applications and improvement of certain operational aspects, such as with pulsed lasers or high‐power continuous‐wave lasers. In recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 134 publications
0
30
0
Order By: Relevance
“…[ 45,46 ] and from Figure 1 d, we found that the linear absorption of BP is thus 16.2%, 13.6%, and 11.3% at 639 nm, 1.06 µm, and 2.1 µm, respectively. Therefore, the largest pulse energy was achieved for Tm:Ho:YGG at 2.1 µm, and Nd:GdVO 4 had the smallest pulse energy at 1.06 µm, which agrees well with the experimetal results: 221 nJ at 2.1 µm, 70.4 nJ at 1.06 µm, and 104 nJ at 639 nm.…”
Section: Bp Optical Modulation Of Visible To Mid-infrared Lasersmentioning
confidence: 94%
“…[ 45,46 ] and from Figure 1 d, we found that the linear absorption of BP is thus 16.2%, 13.6%, and 11.3% at 639 nm, 1.06 µm, and 2.1 µm, respectively. Therefore, the largest pulse energy was achieved for Tm:Ho:YGG at 2.1 µm, and Nd:GdVO 4 had the smallest pulse energy at 1.06 µm, which agrees well with the experimetal results: 221 nJ at 2.1 µm, 70.4 nJ at 1.06 µm, and 104 nJ at 639 nm.…”
Section: Bp Optical Modulation Of Visible To Mid-infrared Lasersmentioning
confidence: 94%
“…On account of the advantages of large pulse energy, short pulse duration, and high peak power, pulse lasers, including mode-locking and Q-switching, receive more widespread attention [2,3]. Pulsed lasers with the pulse width from nanosecond to subpicosecond scales play a key role in the industrial machining, remote sensing, and military defense areas [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed lasers with the pulse width from nanosecond to subpicosecond scales play a key role in the industrial machining, remote sensing, and military defense areas [4]. Ultrashort femtosecond lasers have significant applications in the fields of the in-situ detection, complex reaction dynamics, medical survey, and telecommunication [3]. Passive pulse modulation could be operated with compact and cost-effective structures, such that it has become an influential research direction in the laser field.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to 36(= 3N Z Br ) zone center vibrational degrees of freedom (at k = 0) described by the D4h19 ‐irreducible representation (see, e.g., Refs. ): Γ 36 = 2A 1g + 4B 1g + B 2g + 5E g + A 2g + B 1u + A 1u + 2B 2u + 4A 2u + 5E u . Amongst them, the first four species (2A 1g + 4B 1g + B 2g + 5E g ), which belong to the internal vibrations of the tetrahedral [VO 4 ] 3− units, are Raman‐active modes.…”
Section: Impulsive Srs Lasingmentioning
confidence: 99%